Experiências e condições de trabalho de profissionais de enfermagem no cuidado a pessoas com Covid-19 - Silva, Wilton José de Carvalho (2021)
The World Health Organization declared, on January 30, 2020, Covid-19 as a public health emergency and characterized it as a pandemic. Nursing professionals were exposed to physical, biological and emotional risks, as they participate in the front line of care provided to patients with suspicion or diagnosis of this disease. The study aimed to understand the experiences and working conditions of nursing teams working in hospital institutions in the care of individuals with suspected or diagnosed Covid-19. This is qualitative research, carried out with twenty nursing professionals from two public hospitals of the Western Macroregion of Paraná. Data collection took place between November 2020 and March 2021, through semi-structured interviews, using the WhatsApp application. Data analysis was performed by thematic content analysis. The results found were presented through two articles entitled: Experience of the nursing team's performance in caring for individuals with covid-19 and Work conditions of nursing professionals working in hospitals. The categories present in the first article were: From new demands to successive reflections on the care of individuals with Covid-19; Discomforts inherent to acting in care; Risk of contamination and the complexity of patient care with Covid-19; Emergency hiring and the impact on assistance; Motivation to continue. The ones covered in the second article were: Working conditions regarding the physical structure; Working conditions regarding physical, psychological, and emotional wear; Working conditions regarding the quality and availability of EPIS; Working conditions regarding the demand for assignments; Working conditions regarding social/family distancing. It was possible to know the experiences and working conditions of nursing professionals in the study. It was found that, for the care of people with suspected or diagnosed Covid-19, new work demands, new protocols, and new care flows were incorporated into the routine of professionals, in addition to new hires. However, it is pointed out that, for the performance of these professionals not to imply risks to patient safety, particularly for critically ill patients, adequate training and continuing education in health are required, linked to the field of work. To ensure the safety and comfort of nursing professionals who work in the Covid-19 unit, it is required to offer personal protective equipment in adequate quantity and quality. It is noteworthy that the professionals were motivated by the intention of caring for and recovering people, and showed solidarity and empathy with their professional colleagues. The experience of working in the care of people with Covid-19, with imminent risk of death and the social and family distance allowed the professionals to review important aspects of their lives and to increase their commitment to the profession and nursing care. It is recommended to expand the study to other institutions, with the participation of other health professionals.